COGNITIVE PROCESS OF THE STUDENTS IN WRITING ARGUMENTATIVE TEXT - Sapitri, Reni (Universitas Nusantara PGRI Kediri, 2017)
This study examined whether cognitive process ( students majoring in social and natural science) influences their writing in argumentative text. In qualitative research designs, the researcher administered writing test with five various topics in argumentative text form and then conducted a retrospective interview. The subjects were the students of SMA Negeri 1 Padangsidimpuan from two different majors, Natural Science Major and Social Science Major. The analysis showed that the cognitive processes of the students from the two majors were different in planning, translating and reviewing. The cognitive processes of the students were different because they have different ability in the proficiency of writing, vocabulary and discourse comprehension.